MARAKNYA FENOMENA PENGUNGKAPAN DIRI YANG BERLEBIHAN ATAU OVERSHARING DI MEDIA SOSIAL: PERSPEKTIF SOSIOLOGI - Nadya Meisya Adibrata; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
Rapid developments in information technology have significantly increased the convenience and efficiency of everyday life. Innovations such as mobile phones and other smart devices have changed the way we communicate, allowing for near-constant internet connections and unlimited access to information. Among the various technological innovations that have emerged, social media stands out as one of the most influential aspects. Through their social media accounts, users have the ability to publish various aspects of their personal lives, both in the form of photos and videos, without facing significant obstacles. However, this freedom is often not accompanied by sufficient awareness of privacy. As a result, the phenomenon of oversharing has become widespread. Therefore, this article will discuss the phenomenon of oversharing from a sociological perspective. Using a descriptive qualitative research method with a library data collection method, researchers found that the phenomenon of oversharing is triggered by various factors rooted in sociology, including; Need for Social Validation, Formation of Online Identity, and FOMO (Fear of Missing Out).